ARTIFICIAL INTELLIGENCE, ITS KNOWLEDGE, ATTITUDE, AND PERCEPTIONS AMONG FUTURE HEALTH CARE WORKFORCE - UNDERGRADUATES IN A GOVERNMENT MEDICAL COLLEGE - Swarnalata ,; Dr. Sridevi Garapati,; Dr. Sujatha Peetala,; Dr. Rambabu Rampatruni, (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Artificial Intelligence (AI) has emerged as Metamorphosis in the field of medicine, having the potential to revolutionize diagnostics, treatment, and healthcare delivery. To be ready for new roles and tasks, medical students will need to understand the fundamentals of AI. Knowledge, attitude, and perceptions of AI among undergraduate medical students is crucial, as they represent the future healthcare workforce. Objectives: 1. To assess the knowledge of AI concepts and its applications among undergraduate medical students. 2. To know the attitude and perceptions of medical students towards AI in medicine. Materials and Methods: Cross-sectional online survey was conducted among undergraduate medical students in Rangaraya Medical college, Kakinada, Andhra Pradesh using semi-structured questionnaire between October and December 2023. The questionnaire was designed to assess their knowledge, attitude towards AI in healthcare, and perceptions about AI's impact on the medical profession. Data was collected from clinical year medical students who gave consent and willing to participate in the study. Analysis done by Microsoft Excel 2010 & SPSS Version 21. Data analysis involved descriptive statistics, chi-square tests to identify factors associated with AI knowledge, attitudes, and perceptions. Results: A total of 220 medical students participated, most of them (63.8%) were females. Mean age of the participants was 21±0.84yrs. Of these, most of the students (85.5%) knew about AI whereas 54.1% do not know the application of AI in medicine. In addition, 45% of students agreed that AI will reduce errors in diagnosis, 52.8 – 67.7% agreed that AI is essential in both pathological and radiological diagnostic techniques. More than 1/3rd (39.5%) agreed to include AI in the medical curriculum. However, 58% of the students expressed the fear of replacement of doctor with AI. Furthermore, most of them perceived that AI being subjected to loss of data privacy (75.2%), cyber security attacks (85.8%) and less human interaction with the patient (93.1%). In the present study significant difference was observed with Gender in relation to AI related knowledge (P